Effect of endobronchial coils vs usual care on exercise tolerance in patients with severe emphysema: the RENEW randomized clinical trial - Sciurba, Frank; Herth, Felix (The journal of the American Medical Association, 2016)
Preliminary clinical trials have demonstrated that endobronchial coils compress emphysematous lung tissue and may improve lung function, exercise tolerance, and symptoms in patients with emphysema and severe lung hyperinflation. To determine the effectiveness and safety of endobronchial coil treatment.
Gesehen am 27.05.2020